Encapsulation of lycopene in emulsions and hydrogel beads using dual modified rice starch: Characterization, stability analysis and release behaviour during in-vitro digestion. (July 2020) - Jain, Surangna; Winuprasith, Thunnalin; Suphantharika, Manop
Abstract: The application of lycopene, a potent antioxidant, is limited because of its hydrophobic nature and low chemical stability. To overcome this, different delivery systems, i.e. oil-in-water emulsions and alginate beads, have been synthesized in this study using modified rice starch for improving the stability of lycopene. Lycopene solution (in oil) was used as a control. Modified rice starch was used as it is cheap, GRAS, has better adsorption at the oil-water interface and provides higher resistance to the encapsulated lycopene against the harsh environment of the gastrointestinal tract. During storage at different temperatures (4–70 °C) for 15 days, the lycopene degradation rate was found to increase with increasing storage temperature for all delivery systems and with the type of delivery systems in the following order: solution > emulsion > alginate beads. Further, the delivery systems were passed through a simulated gastrointestinal tract (GIT) model to study the extent of lipid digestion and lycopene bioaccessibility. A positive correlation was observed between the rate and extent of lipid digestion and lycopene bioaccessibility. A significantly higher bioaccessibility of lycopene was observed for the emulsions (20.2%) over the beads (15.6%), whereas the chemical stability of lycopene was found to be significantly higher in the alginate beads (35.6%) than in the emulsions (29.5%). Overall, the results obtained suggest that the modified rice starch can be used as an innovative food-grade material for the design of different delivery systems to improve the chemical stability of lycopene and its controlled release in the gastrointestinal tract. Graphical abstract: Image 1 Highlights: Lycopene was encapsulated in emulsions and alginate beads using modified rice starch. Lycopene encapsulated in alginate beads had higher storage stability than in emulsions. Gastrointestinal fate of lycopene loaded emulsions and alginate beads was studied. Lycopene loaded in alginate beads was more stable than in emulsions in GIT model. Lycopene in emulsions had higher bioaccessibility than in alginate beads in GIT model.